Alzheimer’s disease, neural stem cells and neurogenesis: cellular phase at single-cell level - Cosacak, Mehmet Ilyas (Neural Regen Res, 2019)
Alzheimer’s disease cannot be cured as of yet. Our current understanding on the causes of Alzheimer’s disease is limited. To develop treatments, experimental models that represent a particular cellular phase of the disease and more rigorous scrutiny of the cellular pathological mechanisms are crucial. In recent years, Alzheimer’s disease research underwent a paradigm shift. According to this tendency, Alzheimer’s disease is increasingly being conceived of a disease where not only neurons but also multiple cell types synchronously partake to manifest the pathology. Knowledge on every cell type adds an alternative approach and hope for the efforts towards the treatment. Neural stem cells and their neurogenic ability are making an appearance as a new aspect of the disease manifestation based on the recent findings that neurogenesis reduces dramatically in Alzheimer’s disease patients compared to healthy individuals. Therefore, understanding how neural stem cells can form new neurons in Alzheimer’s disease brains holds an immense potential for clinics. However, this provocative idea requires further evidence and tools for investigation. Recently, single cell sequencing appeared as a revolutionary tool to understand cellular programs in unprecedented resolution and it will undoubtedly facilitate comprehensive investigation of different cell types in Alzheimer’s disease. In this mini-review, we will touch upon recent studies that use single cell sequencing for investigating cellular response in Alzheimer’s disease and some consideration pertaining to the utilization of neural regeneration for Alzheimer’s disease research.